2021
DOI: 10.1037/dev0001261
|View full text |Cite
|
Sign up to set email alerts
|

Executive functions and science achievement during the five-to-seven-year shift.

Abstract: Executive functions (EF) are domain-general cognitive skills that predict school success. However, less is known about the relation between EFs and science achievement. The present study examined the bidirectional associations between science achievement and children's cognitive flexibility and working memory in a nationally representative sample of children in the United States (ECLS-K: 2011; N = 18,174). Using random intercepts cross-lagged panel modeling, results revealed a heterogeneous pattern of associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…For verbal working memory and math, some have revealed their mutualism (Kahl et al, 2022; Mareva et al, 2022), whereas Miller‐Cotto and Byrnes (2020) found no such mutualism. To our knowledge, only one study (Kim et al, 2021) has investigated the potential mutualism between verbal working memory and science and has found such mutualism. The findings of prior studies are inconsistent and thus whether mutualism exists between verbal working memory and academic skills remains unclear.…”
Section: Mutualism Theory In Educationmentioning
confidence: 99%
“…For verbal working memory and math, some have revealed their mutualism (Kahl et al, 2022; Mareva et al, 2022), whereas Miller‐Cotto and Byrnes (2020) found no such mutualism. To our knowledge, only one study (Kim et al, 2021) has investigated the potential mutualism between verbal working memory and science and has found such mutualism. The findings of prior studies are inconsistent and thus whether mutualism exists between verbal working memory and academic skills remains unclear.…”
Section: Mutualism Theory In Educationmentioning
confidence: 99%
“…As mentioned earlier, mutualism theory suggests a possible cognitive-academic bidirectional model (e.g., Kim, Bousselot, & Ahmed, 2021;Peng & Kievit, 2020;Van Der Maas et al, 2006;Zhang & Peng, 2023). In early development, the accumulation and automatic retrieval of domain-specific knowledge are not well established, and students are more likely to invest their cognitive abilities in the more abstract acquisition of learning in general.…”
Section: Domain-specific Approach Of Working Memory Trainingmentioning
confidence: 99%
“…The transition to kindergarten is characterized by a period of rapid change for young children. For many, kindergarten marks the first time children are expected to attend to direct skills undergo rapid development during the early school transition period (Kim et al, 2021; mathematical development. For example, U.S. national test scores suggest that children make the most rapid gains in math achievement during the first few years of formal schooling compared to later developmental periods, including during late childhood and adolescence (Bloom et al, 2008;LoGerfo et al, 2006).…”
Section: The Role Of Executive Function In Shaping the Longitudinal S...mentioning
confidence: 99%